Handbook development and evaluation of the Well@School online course - Notara, Venetia; Lahti, Mari; Laaksonen, Camilla; Korhonen, Joonas; Erjavec, Karmen; Grubliauskienė, Jūratė; Istomina, Natalja; Ivanova, Svetla; Kregar-Velikonja, Nevenka; Lalova, Valentina; Makutienė, Monika; Gergana, Petrova; et al. (Scientific Council of the General Hospital of Piraeus Tzaneion, 2025)
Background: Mental health problems remain a critical issue in young ages. It is documented that health and school professionals need continuous training on how to confront and promote mental health among primary school children. Within the Well@School project, an online course was co-created to develop health professionals’ and primary school professionals’ competences on mental health promotion. The aim of this study was to evaluate the handbook of the Well@School online course.
Material-Methods: Focus groups were conducted in the five partners-countries (i.e. Bulgaria, Greece, Finland, Lithuania and Slovenia). Primarily, school professionals completed an online course and afterwards they participated in a pilot of the handbook. The focus groups were facilitated by the project research team members, and they were conducted in national languages. Content analysis was carried out for the analysis of the collected data.
Results: Positive results were obtained regarding the content and the methods presented in the handbook. Specifically, the content was considered as useful in the provision of knowledge related to mental health issues, the layout motivated participants to go throughout the whole content. They found useful and applicable the methods on how to promote mental health effectively.
Conclusions: This handbook supports the use of the Well@School online course and is applicable to current and future health professionals and professionals working in school settings. It provides a baseline from which innovative e-learning and teaching materials and pedagogical practice can be used.